Advances and challenges in developing andrographolide and its analogues as cancer therapeutic agents. Issue 9 (September 2019) - Soo, Hon Liong; Quah, Shun Ying; Sulaiman, Ibrahim; Sagineedu, Sreenivasa Rao; Lim, Jonathan Chee Woei; Stanslas, Johnson
Highlights: New semisynthetic molecules derived from AGP in recent years to target cancer have not been discussed in any review thus far. With 20 years of research experience in the various therapeutic potentials of andrographolide and its analogues, we compile and review the successful development and mechanisms of action of these promising compounds as anticancer agents. Our review enables readers to learn the key structural moieties in AGP and its analogues that produce greater efficacy and less toxicity in patients. The AGP analogues that deserve further investigation in cancer models are emphasized. Past and ongoing clinical trials are discussed to highlight the therapeutic potential of these molecules. Abstract : Andrographolide (AGP), a naturally occurring bioactive compound, has been investigated as a lead compound in cancer drug development. Its multidimensional therapeutic effects have raised interest among medicinal chemists, which has led to extensive structural modification of the compound, resulting in analogues with improved pharmacological and pharmaceutical properties. Nevertheless, the analogues with the improved properties need to be rigorously studied to identify drug-like lead compounds. We scrutinised articles published from 2012 to 2018, to objectively provide opinions on the mechanisms of action of AGP and its analogues, as well as their potential as viable anticancer drugs. Preclinical and clinical data, along with the extensive medicinal chemistry efforts, indicate the compounds are potential anticancer agents with specific value in treating recalcitrant cancers such as pancreatic and lung cancers.